2016
DOI: 10.1038/aps.2015.137
|View full text |Cite
|
Sign up to set email alerts
|

P2Y receptor-mediated transient relaxation of rat longitudinal ileum preparations involves phospholipase C activation, intracellular Ca2+ release and SK channel activation

Abstract: Aim: Purinergic signaling plays a major role in the enteric nervous system, where it governs gut motility through a number of P2X and P2Y receptors. The aim of this study was to investigate the P2Y receptor-mediated motility in rat longitudinal ileum preparations. Methods: Ileum smooth muscle strips were prepared from rats, and fixed in an organ bath. Isometric contraction and relaxation responses of the muscle strips were measured with force transducers. Drugs were applied by adding of stock solutions to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…diffusion issues through tissues or brain slices (Kroigaard et al, 2012;Chien and Su, 2015;Mader et al, 2016) or perhaps when administering to whole animals (Diness et al, 2011). The consequence is that these drugs may also inadvertently block muscarinic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…diffusion issues through tissues or brain slices (Kroigaard et al, 2012;Chien and Su, 2015;Mader et al, 2016) or perhaps when administering to whole animals (Diness et al, 2011). The consequence is that these drugs may also inadvertently block muscarinic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Radioligand competition assays (using 125 I-Apamin) similarly indicate high affinity binding of UCL1684 with Ki of 1 nM for SK2 and 7.7 nM for SK3 channels ( Benton D.C. et al., 2013 ). Despite high affinity to SK channels, micromolar concentrations of UCL 1684 are sometimes used to overcome diffusion issues through tissues or brain slices ( Kroigaard et al., 2012 ; Benton M. D. et al., 2013 ; Chien and Su, 2015 ; Mader et al., 2016 ) or perhaps when administering to whole animals ( Diness et al., 2011 ). The consequence is that these drugs may also inadvertently block muscarinic responses.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that electrical stimulation of inhibitory nerve cells releases inhibitory neurotransmitters that induce the inhibitory junction potential (IJP) of colonic circular muscle cells. Inhibitory neurotransmitter-induced IJP-mediated colonic smooth muscle relaxation can occur in two ways- a purinergic, large amplitude, fast IJP (fIJP), and a NO-dependent subdued, low amplitude slow IJP (sIJP) [ 9 11 ]. ATP transmitter serves as an essential component of purinergic signaling across the enteric musculomotor nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
“…In the GI, ATP regulates the functional activity of the colonic P2Y 1 receptors by acting as one of the ligands [ 12 ]. The fIJP is highly sensitive to the P2Y 1 receptor antagonist 2-iodo-N6-methyl-(N)-methanocarba-2’-deoxyadenosine-3’,5’-bisphosphate (MRS2500), while sIJP exhibits a higher sensitivity to the NO synthase inhibitor N G -nitro-L-arginine methyl ester (L-NAME) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, PLC generates inositol trisphosphate (IP3) and afterwards IP3 releases Ca 2+ from intracellular stores (Webb et al, 1993;Filtz et al, 1994;Simon et al, 1995). Inhibitory P2Y1 receptors in the gut work through the same Gq/PLC/IP3/Ca 2+ i signaling pathway which leads to the downstream activation of Ca 2+ -dependent and apamin-sensitive K + -channels (KCa, SK-type), followed afterwards by the closure of voltage-sensitive Ca 2+ -channels (CaV, L-type) and the relaxation of smooth muscle tone (Beyder and Farrugia, 2012;Goyal et al, 2013;Burnstock, 2014;Sanders et al, 2014;Kennedy, 2015;King, 2015King, , 2021Mader et al, 2016). Evidence supports the presence of SK2 and SK3 channels on SMCs (Klemm and Lang, 2002), with SK3 channels also present on intramuscular fibroblast-like PDGFR +cells (Sanders et al, 2012(Sanders et al, , 2014Baker et al, 2015), whereas L-type Ca 2+ -channels are found on SMCs as well as on intramuscular ICC/Kit + cells (Beyder & Farrugia, 2012).…”
Section: Introductionmentioning
confidence: 99%